Identification of Ovine KRTAP28-1 and Its Association with Wool Fibre Diameter - Bai, Lingrong (Animals (Basel), 2019)
SIMPLE SUMMARY: Keratin-associated proteins (KAPs) are fundamental components of wool and hair fibres. They are split into three broad groups: the high sulphur (HS), the ultra-high sulphur (UHS) and the high glycine-tyrosine (HGT) KAPs. KRTAP25-1 encodes a HS-KAP protein and the gene has recently been identified in humans. Here, we report the absence of a KRTAP25-1 in sheep, and we describe a new HS-KRTAP (named KRTAP28-1) in the chromosome region where KRTAP25-1 was expected to be found. Six variants (A−F) of KRTAP28-1 containing eight single nucleotide polymorphisms (SNPs) and a TG dinucleotide repeat polymorphism were detected. One SNP was located upstream of the start codon and all the others were non-synonymous SNPs, including a nonsense SNP. The TG repeat polymorphism would lead to a reading frame shift at the carboxyl-terminal end. The association of KRTAP28-1 with wool traits was investigated with 383 Southdown × Merino-cross lambs from seven sire lines. Of the four genotypes with a frequency over 5%, lambs of genotypes AB and BD produced wool of a smaller mean fibre diameter (MFD) than lambs of genotype BC. This shows that KRTAP28-1 is associated with a key wool trait, and variation in this gene might therefore have value as a marker for improving that trait. ABSTRACT: Keratin-associated proteins (KAPs) are a diverse group of proteins and form a matrix that cross-links keratin intermediate filaments in hair and wool fibres. From over 100 KAP genes (KRTAPs) identified in mammalian species, KRTAP25-1 is a high sulphur (HS)-KAP gene, which has recently been described in humans. Here, we report the absence of KRTAP25-1 in sheep, and describe a new HS-KRTAP (named KRTAP28-1) in the chromosome region where KRTAP25-1 was expected to be found. Six variants (A−F) of KRTAP28-1 containing eight single nucleotide polymorphisms (SNPs) and a TG repeat polymorphism were detected. One was positioned 30 bp upstream of the transcription start codon and all the others were non-synonymous SNPs, including a nonsense SNP. The TG repeat polymorphism would lead to a reading frame shift at the carboxyl-terminal end. The effect of KRTAP28-1 on wool traits was investigated with 383 Southdown × Merino-cross lambs from seven sire lines. Of the four genotypes with a frequency of over 5%, lambs of genotypes AB and BD produced wool of a smaller MFD than lambs of genotype BC. This shows that KRTAP28-1 is associated with wool fibre diameter, and that variation in this gene might have potential for use as a gene marker for reducing wool fibre diameter.